Water value, water demand and WFD implementation in an olive intensive Guadalquivir sub-basin - Mesa-Jurado M.A.; Berbel J. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Guadalbullon river sub-basin belongs to the Guadalquivir basin and is an example of intensive olive cultivation. The value of water in the sub-basin is analyzed under different scenarios by integrating an agronomic model (water production function of olive), an economic model of farm results and a sub-basin hydrologic model of water use and river flow. The result shows that the value of water for olive oil production (net margin per m3) is in the range of 0.60 €/m3 - 2.0 €/m3. The impact of minimum flow requirement constraints supposes a reduction of the gross added value of the irrigated olives equalling some 1.2 million Euros per year at sub-basin level.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)